Analisis Kinerja Website Info PBB Badan Pengelolaan Pendapatan Daerah Menggunakan Metode PIECES - Miftahul Jannah; Resad Setyadi (STMIK Budi Darma, 2023)
In Pemalang Regency, the Regional Revenue Management Agency (BAPENDA) manages local taxes. At BAPENDA there is a website that is used to view and check Land and Building Tax (PBB) information called the PBB info website. However, there are still some perceived obstacles such as slow loading times, long page switching and an unattractive appearance. Therefore, an analysis of the PBB information website is needed. Website analysis can be used as a reference in developing a better website. Data collection uses observation, discussions with website admins and users as well as distributing questionnaires to website users. The method used in the analysis of PBB info websites is the PIECES method. The PIECES method is an analytical method for assessing website performance and obtaining specific issues. Based on the test results on the 6 PIECES dimensions, the performance, information, economic, control and efficiency dimensions are included in the satisfied category. And the service dimension is included in the very satisfied category. Apart from analyzing using the PIECES method, it also uses the Pingdom Website Speed ??Test measuring tool to measure website speed, and produces grade 92 (grade A), which means that the website has good PBB information in website speed/performance. Then the Google Transparency Report measuring tool to measure website security concludes that the website is safe. However, there are still aspects that must be considered, namely the dimensions of performance and efficiency so that the PBB info website can increase the speed of service features. In addition, improving facilities and infrastructure at the Pemalang Regency BAPENDA such as changing computers or adding mbps so that the network is stable